Frontiers of philosophy: Thinking at the margin of institutions - Vinola, Sthépane (2023)
The problem of borders is essential to philosophy since, since Plato, it defines its activity as an ontological cut, which makes all philosophy a geo-philosophy. The philosopher is one who dreams of being able to establish clear and precise ontological borders in order-to-order reality, through concepts (fair/unfair, sensible/intelligible, dog/wolf, sophist/philosopher, etc.). This internal importance of borders has an impact on the external borders of philosophy, that is, on the places where it is legitimate to philosophize: academy, kindergarten, high school, university, agora. Thanks to Derrida's philosophy, the author shows that, since philosophy can no longer appear as the guarantor of conceptual frontiers, one must also reassess its external frontiers and assume that philosophy is, by definition, marginal, which implies that it is time to take it back out of the only academic field to take it, where it always was: throughout the city.